GRAPHIC NOVEL REVIEW — THE ADVENTURES OF JOHNNY BUNKO: THE LAST CAREER GUIDE YOU’LL EVER NEED - Weiner, Robert G. (Dialogue, 1(1), 2014)
In the world of higher education, the last 10 years have seen an explosion in the scholarly study of sequential art, sometimes dubbed comics studies. The present number of courses related to comics is probably triple what it was 20 years ago: courses from the freshman to the graduate level, courses in departments as varied as History, Sociology, Film, Gender and Race Studies, Communication, Art, Electronic Media, and Philosophy. The study of comics is where the study of films was 30 years ago. The rise in scholarly monographs has exploded, and there are numerous academic journals devoted to the subject with more popping up all the time. Comic studies, currently, is a popular topic for academics to discuss, teach, and write about...
Keywords: Type of access: Open Access